Excipient Induced Unusual Phase Separation in Bovine Serum Albumin Solution An Explicit Role Played by Ion-Hydration - Bhattacharya, Indrani (Langmuir : the ACS journal of surfaces and colloids, 2024)
We report an instantaneous room-temperature phase separation of 1 mM bovine serum albumin solution in the presence of (20% acetic acid+0.2 M NaCl), a routinely used food preservative; an opaque liquid-like phase (L) coexists in equilibrium with a granular gel like phase (G). Interestingly, neither 20% acetic acid nor 0.2 M NaCl individually induces such a phase separation. Field emission scanning electron microscopy (FESEM) and high-resolution transmission electron microscopy (HRTEM) imaging show aggregated proteins to be dispersed in the upper phase, while the lower phase is composed of cross-linked fibrils (hydrogels). Mid-IR FTIR, Raman scattering, and circular dichroism (CD) experiments reveal a significant increase in the β-sheet content in BSA, which confirms the formation of amyloids in the presence of the excipient. Both L and G phases undergo distinct visual and microscopic changes upon incubation at 25 and 80 °C. It is evident that the added salt plays a pivotal role in bringing about this otherwise unique phase behavior. We divulge the explicit role of the ion associated hydration using THz-FTIR measurements in the 1.5-16.7 THz (50-550 cm-1) frequency window. Systematic alteration in the ion-induced THz-active mode of water envisions the key role of ions in shaping the various phases. Our study depicts an intriguing observation of severe amyloidosis of BSA upon the addition of a food preservative, even at room temperature, which is expected to add new insight into amyloid research. Considering the increasing number of individuals suffering from several neurodegenerative disorders (Alzheimer's, Parkinson's, type-2 diabetes, obesity, cancer, etc.), this study leads a caution toward critically revisiting the usage of known food preservatives